Repair explosion-proof membrane for solar module glass as well as preparation method and application of repair explosion-proof membrane

By designing a repair explosion-proof film for solar module glass, the cracks and bursting problems caused by the difference in the expansion coefficient of glaze and glass during the sintering process of double-glass solar photovoltaic modules are solved, and the low-cost on-site repair of the components is achieved and the service life is extended.

CN119842334APending Publication Date: 2025-04-18CYBRID TECHNOLOGIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411995380.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the sintering process, existing double-glass solar photovoltaic modules do not release stress due to the difference in the expansion coefficient between the glaze and glass, which is prone to cracks and bursts, resulting in component failure and high replacement costs.

Method used

A repair explosion-proof film for solar module glass is designed, including a transparent weathering film, an adhesive layer, a core layer and a transparent weathering functional adhesive layer. The damaged grid glass is repaired through the explosion-proof film of this structure.

Benefits of technology

The explosion-proof membrane can maintain the normal operation of the components during the warranty period, and can be constructed on site, which is cheap, solving the problems of easy damage to components and high replacement costs in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842334A_ABST
    Figure CN119842334A_ABST
Patent Text Reader

Abstract

The invention provides a repairing explosion-proof membrane for solar module glass as well as a preparation method and application of the repairing explosion-proof membrane. The repairing explosion-proof film for the solar module glass comprises a transparent weather-proof film, a bonding layer, a core layer and a transparent weather-proof functional adhesive layer which are attached to one another, the transparent weather-proof functional adhesive layer is prepared from the following raw materials in parts by weight: 100 parts of acrylate prepolymerization liquid, 0.01 to 1 part of cross-linking agent, 0.5 to 1.5 parts of initiator, 0.5 to 3 parts of antioxidant and 0.5 to 5 parts of ultraviolet absorbent. The repair explosion-proof membrane for the solar module glass provided by the invention can be used for repairing damaged grid glass, so that a damaged grid double-glass module can operate normally within a guarantee period, and the repair explosion-proof membrane for the solar module glass can be constructed on site and is low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive tapes, and in particular relates to a repair explosion-proof film for solar module glass and a preparation method and application thereof. Background Art

[0002] In order to utilize the light passing between the cells and increase the power generation efficiency of the existing double-glass solar photovoltaic modules, a grid is printed on the glass surface. However, the compressive stress of the grid part is small when the glass is glazed. During sintering, the white grid reflects the heat radiation performance. The grid area and the transparent glass area are heated differently and at different temperatures. There is a large interface stress between the two. The compressive stress at the edge of the grid changes suddenly. During sintering, when the white grid transitions inward to the transparent glass, the stress at the edge of the grid will change suddenly, especially at the cross point of the white grid, where the stress change is greater. The difference in shrinkage between the glaze and the glass, especially during sintering, high temperature and high pressure, the glaze itself has a large difference in expansion coefficient with the glass, resulting in a large unreleased stress in the glaze part during tempering. The above reasons will cause the glazed glass to crack and burst easily, resulting in a high probability of self-explosion of the double-glass modules produced based on it, causing the module to fail and be unusable, resulting in huge losses.

[0003] At present, there is no suitable repair method for the damaged parts of this type of grid double-glass components. The only option is to replace all the damaged components. If a large number of replacements are required, the cost will be extremely high, causing huge losses. At the same time, the waste components are difficult to recycle and easily cause environmental pollution.

[0004] Therefore, how to provide a low-cost repair explosion-proof film that can repair damaged grid glass and can be constructed on site, so that the damaged grid double-glass components can operate normally within the warranty period has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a repair explosion-proof film for solar module glass and a preparation method and application thereof. The present invention designs the structure and composition of the repair explosion-proof film for solar module glass to prepare a repair explosion-proof film for solar module glass with excellent comprehensive performance. The repair explosion-proof film for solar module glass can repair damaged grid glass, so that the damaged grid double glass module can operate normally within the warranty period, and the repair explosion-proof film for solar module glass can be constructed on site with low cost.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a repair explosion-proof film for solar module glass, the repair explosion-proof film for solar module glass comprising a transparent weather-resistant film, an adhesive layer, a core layer and a transparent weather-resistant functional adhesive layer bonded to each other;

[0008] The raw materials for preparing the transparent weather-resistant functional adhesive layer include the following components in parts by weight:

[0009]

[0010] The present invention designs the structure and composition of the repair explosion-proof film for solar module glass, and the prepared repair explosion-proof film for solar module glass has high light transmittance, suitable peeling bonding strength, high water vapor permeability and excellent electrical performance. The repair explosion-proof film for solar module glass can repair damaged grid glass, so that the damaged grid double-glass module can operate normally within the warranty period, and the repair explosion-proof film for solar module glass can be constructed on site with low cost.

[0011] In the present invention, through the setting of the transparent weather-resistant film, the transparent film has the following advantages: 1. Excellent transparency: the transparent film has a high degree of transparency, which can well display the appearance of the packaged object, making it more beautiful and improving the power generation of the component; 2. Good wear resistance and scratch resistance: the surface of the transparent film has a certain hardness and can effectively resist friction and scratches; 3. Sealing: the transparent film has excellent sealing performance and can effectively block the penetration of moisture, oxygen and other substances; 4. Lightweight and thin film: the transparent film is light in weight and will not add additional burden to the package; 5. High temperature resistance: the transparent film can withstand high temperatures, has good heat sealing performance, and is suitable for various heat-sealed packages.

[0012] In the present invention, the raw materials for preparing the transparent weather-resistant functional adhesive layer are reacted with the main resin through a cross-linking agent. Cross-linking is a process involving the formation of chemical bonds between polymer chains or other macromolecules, creating a three-dimensional network, which significantly enhances the physical and chemical properties of the material, such as strength, elasticity and stability. Improve thermal stability: cross-linking increases the connection points between material molecules, forming a more stable structure, so that the material has higher thermal stability and high temperature resistance. Improve chemical resistance: cross-linking agents can increase the cross-connection points between material molecules, prevent the penetration and dissolution of solvents and chemicals, thereby improving the corrosion resistance and chemical resistance of the material. Adjust the material structure: cross-linking agents can change the connection mode and structure of material molecules, so that the material has different shapes and structures, such as cross-linking linear polymers into a three-dimensional network structure, changing the shape, hardness and elasticity of the material. Improve processing performance: cross-linking agents can improve the rheological properties and processing properties of the material, making the material easy to process and shape, and die-cutting without glue overflow. The weight proportion of the crosslinking agent can be 0.01 part, 0.02 part, 0.05 part, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part, etc.

[0013] In the raw materials for preparing the transparent weather-resistant functional adhesive layer, the initiator acts on the polymerization reaction: after absorbing the energy of ultraviolet light or visible light, the photoinitiator can produce free radicals or cations. These active species can initiate the polymerization, cross-linking and curing of monomers to form a polymer material. Determine the curing rate: the photoinitiator plays a decisive role in the photocuring speed of the photocurable material. They can absorb light of a specific wavelength, obtain a high energy state or an excited state through photoexcitation, and then react with other molecules to produce free radicals or ions and initiate chemical reactions. Improve the curing efficiency: the activity of the photoinitiator can be regulated by changing the intensity and wavelength of the light source, which makes the photocuring process more efficient and controllable. The weight proportion of the initiator can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts, etc.

[0014] In the raw materials for preparing the transparent weather-resistant functional adhesive layer, the oxidation process is delayed or inhibited: the antioxidant can delay or inhibit the oxidation process of the polymer, prevent the aging of the polymer, and thus extend the service life of the material. The weight proportion of the antioxidant can be 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.3 parts, 2.5 parts, 2.7 parts or 3 parts.

[0015] Among the raw materials for preparing the transparent weather-resistant functional adhesive layer, the ultraviolet absorber can absorb ultraviolet rays: the ultraviolet absorber can strongly and selectively absorb the ultraviolet part in sunlight and fluorescent light sources, especially ultraviolet rays with a wavelength of 290-400nm. This absorption effect can protect the material from damage by ultraviolet rays. Protecting materials: the ultraviolet absorber protects the polymer from damage by ultraviolet radiation by absorbing ultraviolet rays, and prevents the material from being excited by the absorption of ultraviolet energy and then undergoing photophysical and photochemical decomposition. Energy conversion: the ultraviolet absorber converts the absorbed ultraviolet energy into heat energy or harmless low-energy radiation and releases it, thereby avoiding damage to the skin and preventing the degradation of high-molecular polymers. Improving product stability: the ultraviolet absorber helps to improve the anti-aging performance of the product and extend the service life of the product, especially in products used outdoors, such as coatings, plastics, etc. Synergistic effect: when the ultraviolet absorber is used together with other light stabilizers (such as HALS), a synergistic effect can be produced to more effectively protect the polymer from damage by ultraviolet rays. Preventing color changes: the ultraviolet absorber can prevent color changes caused by ultraviolet rays and maintain the original color and appearance of the material. The weight proportion of the ultraviolet absorber can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, etc.

[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0017] As a preferred technical solution of the present invention, the raw materials for preparing the acrylic ester prepolymer solution include the following components in parts by mass: 90-110 parts of at least two acrylic monomers and 0.05-0.1 parts of an initiator.

[0018] In the raw materials for preparing the acrylate prepolymer solution, the mass fraction of the acrylic monomer can be 90 parts, 92 parts, 94 parts, 96 parts, 98 parts, 100 parts, 102 parts, 104 parts, 106 parts, 108 parts or 110 parts.

[0019] In the raw materials for preparing the acrylate prepolymer solution, the mass fraction of the initiator can be 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts.

[0020] Preferably, the acrylic monomer is selected from any one of acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, hexyl acrylate, isooctyl acrylate, lauryl acrylate, benzyl acrylate, cyclohexyl acrylate, perfluoroalkyl acrylate, hydroxyethyl phosphate acrylate, isobornyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, isooctyl acrylate, lauryl methacrylate, isobornyl methacrylate, and cyclohexyl methacrylate, or a combination of at least two of them.

[0021] Preferably, the initiator comprises a redox initiator.

[0022] Preferably, the redox initiator comprises an oxidant and a reductant, the oxidant comprises dibenzoyl peroxide, and the reductant is selected from any one of N,N-dimethylaniline, N,N-diethylaniline or N,N-dimethyl-p-benzylamine or a combination of at least two thereof.

[0023] Preferably, the molar ratio of the oxidant to the reductant is (1-2):1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc.

[0024] Preferably, the viscosity of the acrylate prepolymer liquid is 500-10000 cps, for example, 500 cps, 1000 cps, 2000 cps, 3000 cps, 4000 cps, 5000 cps, 6000 cps, 7000 cps, 8000 cps, 9000 cps or 10000 cps.

[0025] In the present invention, the viscosity of the acrylic ester prepolymer solution is tested by referring to the adhesive viscosity test method of GB 2794-81.

[0026] Preferably, the acrylate prepolymer solution is prepared by the following method, which comprises the following steps:

[0027] At least two acrylic monomers and an initiator are mixed to carry out a prepolymerization reaction to obtain the acrylic ester prepolymer solution.

[0028] Preferably, the mixing time is 20-40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min.

[0029] Preferably, the mixing is performed under a protective gas atmosphere, and the protective gas includes nitrogen.

[0030] Preferably, the prepolymerization reaction time is 30-120 min (for example, it can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min, etc.), and the temperature is 30-80°C (for example, it can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.).

[0031] As a preferred technical solution of the present invention, the crosslinking agent is selected from any one of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate or trimethylolpropane triacrylate, or a combination of at least two thereof.

[0032] Preferably, the initiator comprises a thermal initiator or a photoinitiator.

[0033] Preferably, the thermal initiator comprises a peroxide.

[0034] Preferably, the peroxide is selected from any one or a combination of at least two of 1,3-1,4-di(tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-butylisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne, 4,4′-bis(tert-butylperoxy)valerate, 1,1′-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane or 2,4-dichlorobenzoyl peroxide.

[0035] Preferably, the photoinitiator is selected from any one or a combination of at least two of α,α-dimethoxy-α-phenylacetophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, benzophenone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone or a macromolecular thioxanthone initiator.

[0036] As a preferred technical solution of the present invention, the antioxidant is selected from any one of aromatic amine antioxidants, hindered phenol antioxidants or auxiliary antioxidants, or a combination of at least two thereof.

[0037] It should be noted that the present invention does not have any special restrictions on the specific selection of aromatic amine antioxidants, hindered phenol antioxidants, and auxiliary antioxidants, and the above-mentioned types of antioxidants commonly used in the art are all applicable.

[0038] Preferably, the ultraviolet absorber is selected from any one of salicylate ultraviolet absorbers, benzophenone ultraviolet absorbers, benzotriazole ultraviolet absorbers, substituted acrylonitrile ultraviolet absorbers, triazine ultraviolet absorbers and hindered amine ultraviolet absorbers, or a combination of at least two thereof.

[0039] Similarly, the present invention does not have any special restrictions on the specific selection of the above-mentioned types of ultraviolet absorbers, and the above-mentioned types of ultraviolet absorbers commonly used in the art are all applicable.

[0040] As a preferred technical solution of the present invention, the raw materials for preparing the transparent weather-resistant functional adhesive layer also include 0.01-3 parts by weight of a light stabilizer, for example, 0.01 parts by weight, 0.02 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.5 parts by weight, 0.7 parts by weight, 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.7 parts by weight or 3 parts by weight, etc.

[0041] Preferably, the light stabilizer comprises a hindered amine light stabilizer (HALS).

[0042] Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer also include 0.01-3 parts by weight of a water-blocking resin, for example, 0.01 parts by weight, 0.02 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.5 parts by weight, 0.7 parts by weight, 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.7 parts by weight or 3 parts by weight, etc.

[0043] Preferably, the water-blocking resin is selected from any one of chloroprene rubber, butyl rubber, polyisobutylene, styrene block copolymer, polyolefin block copolymer, acrylic copolymer, polyurethane, nitrile rubber or EPDM rubber, or a combination of at least two thereof.

[0044] Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer also include 0.01-3 parts by weight of a nucleating agent, for example, it can be 0.01 parts by weight, 0.02 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.5 parts by weight, 0.7 parts by weight, 1 parts by weight, 1.2 parts by weight, 1.5 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.7 parts by weight or 3 parts by weight, etc.

[0045] Preferably, the nucleating agent is selected from any one or a combination of at least two of fatty carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates and lignin acid and its derivatives or sodium benzoate and bis(p-tert-butylbenzoic acid)carboxyaluminum.

[0046] Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer also include 0.01-3 parts by weight of a transparent flame retardant, for example, 0.01 parts by weight, 0.02 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.5 parts by weight, 0.7 parts by weight, 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.7 parts by weight or 3 parts by weight, etc.

[0047] Preferably, the transparent flame retardant is selected from any one or a combination of at least two of potassium perfluorobutyl sulfonate, potassium diphenylsulfonylbenzene sulfonate, sodium 2,4,5-trichlorobenzene sulfonate, halogen-free aromatic phosphate transparent flame retardants, resorcinol biphenyl phosphate or phosphorus copolymer transparent flame retardants.

[0048] It should be noted that the present invention does not have any special restrictions on the specific selection of halogen-free aromatic phosphate transparent flame retardants and phosphorus-based copolymer transparent flame retardants. The halogen-free aromatic phosphate transparent flame retardants and phosphorus-based copolymer transparent flame retardants commonly used in the art are all applicable.

[0049] Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer also include 1-100 parts by weight of solvent, for example, it can be 1 part by weight, 5 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight or 100 parts by weight, etc.

[0050] Preferably, the solvent is selected from any one or a combination of at least two of aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, ketone solvents or diol derivatives;

[0051] Preferably, the aromatic hydrocarbon solvents include but are not limited to: benzene, toluene, xylene; the aliphatic hydrocarbon solvents include but are not limited to: pentane, hexane or octane; the alicyclic hydrocarbon solvents include but are not limited to: cyclohexane, cyclohexanone, toluene and cyclohexanone; the halogenated hydrocarbon solvents include but are not limited to: chlorobenzene, dichlorobenzene, dichloromethane; the alcohol solvents include but are not limited to: methanol, ethanol, isopropanol; the ether solvents include but are not limited to: ether, propylene oxide; the ester solvents include but are not limited to: methyl acetate, ethyl acetate, propyl acetate; the ketone solvents include but are not limited to: acetone, methyl butyl ketone, methyl isobutyl ketone; the glycol derivative solvents include but are not limited to: ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether.

[0052] In the present invention, the method for preparing the raw material for preparing the transparent weather-resistant functional adhesive layer comprises the following steps:

[0053] The raw material components for preparing the transparent weather-resistant functional adhesive layer are mixed evenly to obtain the raw material for preparing the transparent weather-resistant functional adhesive layer.

[0054] As a preferred technical solution of the present invention, the core layer is selected from any one of PET film, PE film, PP film or transparent polyester film.

[0055] Preferably, the transparent weather-resistant film is selected from any one of a transparent polyvinylidene fluoride film, a transparent polyvinyl fluoride film, a transparent ethylene-tetrafluoroethylene copolymer film, a transparent polychlorotrifluoroethylene film, a transparent polytetrafluoroethylene, a transparent ethylene-chlorotrifluoroethylene copolymer film, a transparent vapor-deposited water vapor barrier film, a transparent sputtered water vapor barrier film, a transparent atomic deposition water vapor barrier film or a transparent polymer water vapor barrier film.

[0056] As a preferred technical solution of the present invention, the thickness of the transparent weather-resistant film is 10-50 μm (for example, it can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc.), preferably 15-30 μm.

[0057] Preferably, the thickness of the core layer is 25-400 μm (for example, it can be 25 μm, 40 μm, 50 μm, 70 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 210 μm, 240 μm, 270 μm, 300 μm, 330 μm, 360 μm or 400 μm, etc.), preferably 15-30 μm, preferably 50-300 μm.

[0058] Preferably, the thickness of the transparent weather-resistant functional adhesive layer is 10-2000 μm (for example, it can be 10 μm, 50 μm, 70 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, 1200 μm, 1400 μm, 1600 μm, 1800 μm or 2000 μm, etc.), more preferably 70-500 μm.

[0059] In the present invention, the role of the adhesive layer is to composite the transparent weather-resistant film and the core layer. The present invention has no special restrictions on the material and thickness of the adhesive layer, and any commonly used transparent adhesive in the art is applicable, including, for example, transparent glue PA3029 provided by Shanghai Weikai Chemical.

[0060] As a preferred technical solution of the present invention, the solar module glass repair explosion-proof film further comprises a release film layer;

[0061] The release film layer is arranged on the side of the transparent weather-resistant functional layer away from the core layer, that is, the solar module glass repair explosion-proof film includes a transparent weather-resistant film, an adhesive layer, a core layer, a transparent weather-resistant functional adhesive layer and a release film layer.

[0062] Preferably, the release film layer is a PET single-sided release film or a grid embossed release film.

[0063] Preferably, the thickness of the release film is 5-200 μm (for example, it can be 5 μm, 10 μm, 12 μm, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm, etc.), preferably 12-50 μm.

[0064] In a second aspect, the present invention provides a method for preparing the repair explosion-proof film for solar module glass as described in the first aspect, the preparation method comprising the following steps:

[0065] After the transparent weather-resistant film, the adhesive layer and the core layer are compounded, the raw materials for preparing the transparent weather-resistant functional adhesive layer are coated on the side of the core layer away from the adhesive layer, and polymerized to obtain the repair explosion-proof film for solar module glass.

[0066] It should be noted that if the solar module glass repair explosion-proof film includes a release film layer, the preparation method of the solar module glass repair explosion-proof film may be:

[0067] The raw materials for preparing the transparent weather-resistant functional adhesive layer are coated between the core layer and the release film layer, and the coating is performed by a three-layer slit coating head, and radiation curing is performed to obtain the repair explosion-proof film for solar module glass.

[0068] In a third aspect, the present invention provides an application of the solar module glass repair explosion-proof film as described in the first aspect, wherein the solar module glass repair explosion-proof film is used for on-site repair of damaged parts of grid double-glass modules.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] The present invention designs the structure and composition of the repair explosion-proof film for solar module glass, and the prepared repair explosion-proof film for solar module glass has high light transmittance, suitable peeling bonding strength, high water vapor permeability and excellent electrical performance. The repair explosion-proof film for solar module glass can repair damaged grid glass, so that the damaged grid double-glass module can operate normally within the warranty period, and the repair explosion-proof film for solar module glass can be constructed on site with low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 1 is a schematic diagram of the structure of a repair explosion-proof film for solar module glass provided in Example 1 of the present invention;

[0072] Among them, 1-transparent weather-resistant film, 2-adhesive layer, 3-core layer, 4-transparent weather-resistant functional adhesive layer, 5-release film layer. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0074] Example 1

[0075] This embodiment provides a repair explosion-proof film for solar module glass and a preparation method thereof. The structural schematic diagram of the repair explosion-proof film for solar module glass is as follows: Figure 1 As shown, it includes a transparent weather-resistant film 1, an adhesive layer 2, a core layer 3, a transparent weather-resistant functional adhesive layer 4 and a release film layer 5 that are bonded to each other;

[0076] The transparent weather-resistant film 1 is a transparent vapor-deposited water vapor barrier film (produced by Toppan Japan, model GL-RD) with a thickness of 25 μm;

[0077] The adhesive layer 2 is made of transparent glue (Shanghai Weikai Chemical, PA3029) and has a thickness of 10 μm;

[0078] The core layer 3 is a transparent polyester film (Yuxing New Material, CY25HT (GU)) with a thickness of 250 μm;

[0079] The thickness of the transparent weather-resistant functional adhesive layer 4 is 200 μm;

[0080] The release film layer 5 is a PET release film with a thickness of 50 μm;

[0081] The raw materials for preparing the transparent weather-resistant functional adhesive layer 4 include the following components in parts by weight:

[0082]

[0083] The raw materials for preparing the acrylate prepolymer liquid include, by weight, 15 parts of acrylic acid, 85 parts of isooctyl acrylate, and 0.05 parts of an initiator (the initiator is composed of dibenzoyl peroxide and N,N-dimethylaniline in a molar ratio of 1:1); the preparation method of the acrylate prepolymer liquid is as follows: in a nitrogen atmosphere, the raw materials for preparing the acrylate prepolymer liquid are mixed for 30 minutes, and a prepolymerization reaction is carried out at 40° C. for 60 minutes to obtain an acrylate prepolymer liquid with a viscosity of 4000 cps;

[0084] The preparation method of the raw materials for the transparent weather-resistant functional adhesive layer 4 is as follows: put the raw material components for the transparent weather-resistant functional adhesive layer in a vacuum stirring kettle, stir and mix for 0.5h at a rotation speed of 7000rpm to obtain the raw materials for the transparent weather-resistant functional adhesive layer.

[0085] The preparation method of the above-mentioned solar panel glass repair explosion-proof film is as follows:

[0086] (1) Using transparent glue, bonding the transparent vapor-deposited water vapor barrier film and the transparent polyester film;

[0087] (2) The raw materials for preparing the transparent weather-resistant functional adhesive layer are coated between the transparent polyester film and the PET release film by using a three-layer slit coating head, and radiation curing is performed under the conditions of ultraviolet light with a wavelength of 320 nm and an intensity of 8000 mJ / cm to obtain the repair explosion-proof film for the solar module glass.

[0088] Example 2

[0089] This embodiment provides a repair explosion-proof film for solar module glass and a preparation method thereof, wherein the repair explosion-proof film for solar module glass comprises a transparent weather-resistant film, an adhesive layer, a core layer, a transparent weather-resistant functional adhesive layer and a release film layer that are bonded to each other;

[0090] The transparent weather-resistant film is a transparent vapor-deposited water vapor barrier film (produced by Toppan Japan, model GL-RD) with a thickness of 25 μm;

[0091] The adhesive layer is prepared from transparent glue (Shanghai Weikai Chemical, PA3029) with a thickness of 5 μm;

[0092] The core layer is a transparent polyester film (Yuxing New Material, CY25HT (GU)) with a thickness of 200 μm;

[0093] The thickness of the transparent weather-resistant functional adhesive layer is 300 μm;

[0094] The release film layer is a PET mesh release film with a thickness of 125 μm;

[0095] The raw materials for preparing the transparent weather-resistant functional adhesive layer 4 include the following components in parts by weight:

[0096]

[0097] The raw materials for preparing the acrylate prepolymer liquid include, by mass, 12 parts of butyl acrylate, 26 parts of methyl acrylate, 2 parts of glycidyl methacrylate, 20 parts of methyl methacrylate, 20 parts of isobornyl methacrylate, 14 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.1 parts of initiator (the initiator is composed of dibenzoyl peroxide and N,N-dimethylaniline in a molar ratio of 1:1), and 200 parts of ethyl acetate, and the viscosity is 8000cps; the preparation method of the acrylate prepolymer liquid is as follows: in a nitrogen atmosphere, mixing the raw materials for preparing the acrylate prepolymer liquid for 30 minutes, and performing a prepolymerization reaction at 50°C for 30 minutes to obtain the acrylate prepolymer liquid;

[0098] The preparation method of the raw materials for the transparent weather-resistant functional adhesive layer is as follows: placing the raw material components for the transparent weather-resistant functional adhesive layer in a vacuum stirring kettle, stirring and mixing for 0.5h at a rotation speed of 7000rpm, to obtain the raw materials for the transparent weather-resistant functional adhesive layer.

[0099] The preparation method of the above-mentioned solar panel glass repair explosion-proof film is as follows:

[0100] (1) Using transparent glue, bonding the transparent vapor-deposited water vapor barrier film and the transparent polyester film;

[0101] (2) The raw materials for preparing the transparent weather-resistant functional adhesive layer are coated between the transparent polyester film and the PET release film by using a three-layer slit coating head, and radiation curing is performed under the conditions of ultraviolet light with a wavelength of 320 nm and an intensity of 8000 mJ / cm to obtain the repair explosion-proof film for the solar module glass.

[0102] Example 3

[0103] This embodiment provides a repair explosion-proof film for solar module glass and a preparation method thereof, wherein the repair explosion-proof film for solar module glass comprises a transparent weather-resistant film, an adhesive layer, a core layer, a transparent weather-resistant functional adhesive layer and a release film layer that are bonded to each other;

[0104] The transparent weather-resistant film is a transparent vapor-deposited water vapor barrier film (produced by Toppan Japan, model GL-RD) with a thickness of 25 μm;

[0105] The adhesive layer was prepared from transparent glue (Shanghai Weikai Chemical, PA3029) with a thickness of 10 μm;

[0106] The core layer is a transparent polyester film (Dongfang Technology, D250) with a thickness of 150 μm;

[0107] The thickness of the transparent weather-resistant functional adhesive layer is 500 μm;

[0108] The release film is a common release film with a thickness of 50 μm;

[0109] The raw materials for preparing the transparent weather-resistant functional adhesive layer 4 include the following components in parts by weight:

[0110]

[0111] The raw materials and preparation method of the acrylic acid ester prepolymer solution are the same as those in Example 2;

[0112] The preparation method of the raw materials for the transparent weather-resistant functional adhesive layer is as follows: placing the raw material components for the transparent weather-resistant functional adhesive layer in a vacuum stirring kettle, stirring and mixing for 0.5h at a rotation speed of 7000rpm, to obtain the raw materials for the transparent weather-resistant functional adhesive layer.

[0113] The preparation method of the above-mentioned solar panel glass repair explosion-proof film is as follows:

[0114] (1) Using transparent glue, bonding the transparent vapor-deposited water vapor barrier film and the transparent polyester film;

[0115] (2) The raw materials for preparing the transparent weather-resistant functional adhesive layer are coated between the transparent polyester film and the PET release film by using a three-layer slit coating head, and radiation curing is performed under the conditions of ultraviolet light with a wavelength of 320 nm and an intensity of 8000 mJ / cm to obtain the repair explosion-proof film for the solar module glass.

[0116] The performance test of the solar module glass repair explosion-proof film provided in the above embodiment and comparative example is carried out, and the test method is as follows:

[0117] (1) Peel strength test: refer to GBT 2792-2014 test method for peel strength of adhesive tape for testing;

[0118] (2) Light transmittance: Tested in accordance with ISO 13468-2;

[0119] (3) Water vapor transmission rate test: refer to GB / T 15331-2020 "Test method for water vapor transmission rate of pressure-sensitive adhesive tapes" for testing.

[0120] (4) Wet leakage test: The test method refers to the standard IEC TS 62804-1. Test conditions: +85℃, relative humidity 85%; -1500V constant DC voltage, DH1000h;

[0121] (5) Appearance: Observe whether there are bubbles in the repair explosion-proof films for solar module glass provided in the above-mentioned embodiments and comparative examples, and record them.

[0122] The performance test results are shown in Table 1.

[0123] Table 1

[0124]

[0125] It can be seen from Table 1 that the double-glass solar panel repair tape provided by the present invention is bubble-free, has a light transmittance of more than 80%, specifically 84.8%-86.4%, and has high bonding strength, peel strength>14N / cm, specifically 15.4N / cm-22.6N / cm, and the peel strength after DH-1000H is 14.6N / cm-21.4N / cm), and has high weather resistance, the initial electrical properties (wet leakage) are 3360MΩ-3645MΩ, and the electrical properties (wet leakage) after DH-1000H are 3225.6MΩ-3353.4MΩ.

[0126] In summary, the present invention designs the structure and composition of the repair explosion-proof film for solar module glass, and the prepared repair explosion-proof film for solar module glass has high light transmittance, suitable peeling bonding strength, high water vapor permeability and excellent electrical properties. The repair explosion-proof film for solar module glass can repair damaged grid glass, so that the damaged grid double-glass module can operate normally within the warranty period, and the repair explosion-proof film for solar module glass can be constructed on site with low cost.

[0127] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A repair explosion-proof film for solar module glass, characterized in that: The solar module glass repair explosion-proof film comprises a transparent weather-resistant film, an adhesive layer, a core layer and a transparent weather-resistant functional adhesive layer that are bonded to each other; The raw materials for preparing the transparent weather-resistant functional adhesive layer include the following components in parts by weight:

2. The explosion-proof repair film for solar module glass according to claim 1, characterized in that: The raw materials for preparing the acrylic ester prepolymer solution include the following components in parts by weight: 90-110 parts of at least two acrylic monomers and 0.05-0.1 parts of an initiator; Preferably, the acrylic monomer is selected from any one of acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, hexyl acrylate, isooctyl acrylate, lauryl acrylate, benzyl acrylate, cyclohexyl acrylate, perfluoroalkyl acrylate, hydroxyethyl phosphate acrylate, isobornyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, isooctyl acrylate, lauryl methacrylate, isobornyl methacrylate, and cyclohexyl methacrylate, or a combination of at least two thereof; Preferably, the initiator comprises a redox initiator; Preferably, the redox initiator comprises an oxidant and a reductant, the oxidant comprises dibenzoyl peroxide, and the reductant is selected from any one or a combination of at least two of N,N-dimethylaniline, N,N-diethylaniline or N,N-dimethyl-p-benzylamine; Preferably, the molar ratio of the oxidant to the reductant is (1-2):1; Preferably, the viscosity of the acrylate prepolymer liquid is 500-10000cps; Preferably, the acrylate prepolymer solution is prepared by the following method, which comprises the following steps: Mixing at least two acrylic monomers and an initiator to perform a prepolymerization reaction to obtain the acrylic ester prepolymer solution; Preferably, the mixing time is 20-40 min; Preferably, the mixing is performed under a protective gas atmosphere, and the protective gas includes nitrogen; Preferably, the prepolymerization reaction time is 30-120 min and the temperature is 30-80°C.

3. The explosion-proof repair film for solar module glass according to claim 1 or 2, characterized in that: The crosslinking agent is selected from any one of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate or trimethylolpropane triacrylate or a combination of at least two thereof; Preferably, the initiator comprises a thermal initiator or a photoinitiator; Preferably, the thermal initiator comprises a peroxide; Preferably, the peroxide is selected from any one or a combination of at least two of 1,3-1,4-di(tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-butylisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne, 4,4′-bis(tert-butylperoxy)valerate, 1,1′-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane or 2,4-dichlorobenzoylperoxide; Preferably, the photoinitiator is selected from any one or a combination of at least two of α,α-dimethoxy-α-phenylacetophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, benzophenone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone or a macromolecular thioxanthone initiator.

4. The explosion-proof repair film for solar module glass according to any one of claims 1 to 3, characterized in that: The antioxidant is selected from any one or a combination of at least two of aromatic amine antioxidants, hindered phenol antioxidants or auxiliary antioxidants; Preferably, the ultraviolet absorber is selected from any one of salicylate ultraviolet absorbers, benzophenone ultraviolet absorbers, benzotriazole ultraviolet absorbers, substituted acrylonitrile ultraviolet absorbers, triazine ultraviolet absorbers and hindered amine ultraviolet absorbers, or a combination of at least two thereof.

5. The explosion-proof repair film for solar module glass according to any one of claims 1 to 4, characterized in that: The raw materials for preparing the transparent weather-resistant functional adhesive layer also include 0.01-3 parts by weight of a light stabilizer; Preferably, the light stabilizer comprises a hindered amine light stabilizer; Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer further include 0.01-3 parts by weight of a water-blocking resin; Preferably, the water-blocking resin is selected from any one or a combination of at least two of chloroprene rubber, butyl rubber, polyisobutylene, styrene block copolymer, polyolefin block copolymer, acrylic copolymer, polyurethane, nitrile rubber or EPDM rubber; Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer further include 0.01-3 parts by weight of a nucleating agent; Preferably, the nucleating agent is selected from any one or a combination of at least two of fatty carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates, lignin acid and its derivatives, or sodium benzoate and bis(p-tert-butylbenzoic acid) carboxyaluminum; Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer further include 0.01-3 parts by weight of a transparent flame retardant; Preferably, the transparent flame retardant is selected from any one or a combination of at least two of potassium perfluorobutyl sulfonate, potassium diphenylsulfonylbenzene sulfonate, sodium 2,4,5-trichlorobenzene sulfonate, halogen-free aromatic phosphate transparent flame retardant, resorcinol biphenyl phosphate or phosphorus copolymer transparent flame retardant; Preferably, the raw materials for preparing the transparent weather-resistant functional adhesive layer further include 1-100 parts by weight of a solvent.

6. The explosion-proof repair film for solar module glass according to any one of claims 1 to 5, characterized in that: The core layer is selected from any one of PET film, PE film, PP film or transparent polyester film; Preferably, the transparent weather-resistant film is selected from any one of a transparent polyvinylidene fluoride film, a transparent polyvinyl fluoride film, a transparent ethylene-tetrafluoroethylene copolymer film, a transparent polychlorotrifluoroethylene film, a transparent polytetrafluoroethylene, a transparent ethylene-chlorotrifluoroethylene copolymer film, a transparent vapor-deposited water vapor barrier film, a transparent sputtered water vapor barrier film, a transparent atomic deposition water vapor barrier film or a transparent polymer water vapor barrier film.

7. The explosion-proof repair film for solar module glass according to any one of claims 1 to 6, characterized in that: The thickness of the transparent weather-resistant film is 10-50 μm, preferably 15-30 μm; Preferably, the thickness of the core layer is 25-400 μm, preferably 50-300 μm; Preferably, the thickness of the transparent weather-resistant functional adhesive layer is 10-2000 μm, more preferably 70-500 μm.

8. The explosion-proof repair film for solar module glass according to any one of claims 1 to 7, characterized in that: The solar module glass repair explosion-proof film also includes a release film layer; The release film layer is arranged on the side of the transparent weather-resistant functional layer away from the core layer; Preferably, the release film layer is a PET single-sided release film or a grid embossed release film; Preferably, the release film has a thickness of 5-200 μm, preferably 12-50 μm.

9. A method for preparing a repair explosion-proof film for solar module glass according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: After the transparent weather-resistant film, the adhesive layer and the core layer are compounded, the raw materials for preparing the transparent weather-resistant functional adhesive layer are coated on the side of the core layer away from the adhesive layer, and polymerized to obtain the repair explosion-proof film for solar module glass.

10. An application of the explosion-proof repair film for solar module glass according to any one of claims 1 to 8, characterized in that: The solar module glass repair explosion-proof film is used for on-site repair of damaged parts of grid double-glass modules.

Citation Information

Patent Citations

  • High-watertightness transparent back and front plates for solar module

    CN106784097A

  • High performance repairing adhesive tape used for photovoltaic module backboards, and preparation method thereof

    CN107267086A

  • Photovoltaic module backboard repairing material and preparation method thereof and repairing method

    CN109517534A

  • Lead carrier film for solar cell module and preparation method thereof

    CN113502010A

  • Adhesive tape for repairing double-glass solar module as well as preparation method and application of adhesive tape

    CN118325495A